Epigenetic regulation of macrophage activation in chronic obstructive pulmonary disease - Zhang, Feng; Cui, Yachao; Zhang, Tiejun; Yin, Wenguang (Frontiers in Immunology, 2024)
Macrophages in the innate immune system play a vital role in various lung diseases such as asthma, chronic obstructive pulmonary disease (COPD), acute lung injury and pulmonary fibrosis. Macrophages involved in the process of immunity need to go through a process of activation, including changes in gene expression and cell metabolism. Epigenetic modifications are key factors of macrophage activation including DNA methylation, histone modification and non-coding RNA regulation. Understanding the role and mechanisms of epigenetic regulation of macrophage activation can provide insights into the function of macrophages in lung diseases and help identification of potential therapeutic targets. This review summarizes the latest progress in the epigenetic changes and regulation of macrophages in their development process and in normal physiological states, and the epigenetic regulation of macrophages in COPD as well as the influence of macrophage activation on COPD development.